Fabrication of non-contact carrier system using solar magnetic suspension - Yuji ISHINO (The Japan Society of Mechanical Engineers, 2015)
A solar-powered magnetic suspension carrier is fabricated which achieves noncontact power supply to the carrier. There are two conventional methods of supplying power to a carrier. One is through wires or contacts such as pantograph and the other is an on-board battery in the carrier. However, the contactless property is lost in the former while stations for charging the on-board battery are necessary in the latter. These problems are overcome by the proposed carrier system using solar magnetic suspension that can achieve continuous levitation. It is assumed for the system to operate indoors like inside a factory building. The generation of power by solar cells is low so that the magnetic suspension needs power saving. A zero power control system is applied to the suspension of the floator. In addition, low-power peripheral devices are also fabricated. The developed carrier system achieved a 24-hour levitation without external power supply in a bright environment.